THE REMARKABLE RE-OS CHRONOMETER IN MOLYBDENITE: HOW AND WHY IT WORKS - Stein H.J.; Markey R.J.; Morgan J.W.; Hannah J.L.; Scherstén A. (My University, 2001)
The Re–Os (rhenium–osmium) chronometer applied to molybdenite (MoS2) is now demonstrated to be remarkably robust, surviving intense deformation and high-grade thermal metamorphism. Successful dating of molybdenite is dependent on proper preparation of the mineral separate and analysis of a critical quantity of molybdenite, unique to each sample, such that recognized spatial decoupling of 187Re parent and 187Os daughter within individual molybdenite crystals is overcome. Highly precise, accurate and reproducible age results are derived through isotope dilution and negative thermal ion mass spectrometry (ID-NTIMS). Spatial decoupling of parent–daughter precludes use of the laser ablation ICP-MS microanalytical technique for Re–Os dating of molybdenite. The use of a reference or control sample is necessary to establish laboratory credibility and for interlaboratory comparisons. The Rb–Sr, K–Ar and 40Ar/39Ar chronometers are susceptible to chemical and thermal disturbance, particularly in terranes that have experienced subsequent episodes of hydrothermal/magmatic activity, and therefore should not be used as a basis for establishing accuracy in Re–Os dating of molybdenite, as has been done in the past. Re–Os ages for molybdenite are almost always in agreement with observed geological relationships and, when available, with zircon and titanite U–Pb ages. For terranes experiencing multiple episodes of metamorphism and deformation, molybdenite is not complicated by overgrowths as is common for some minerals used in U–Pb dating (e.g. zircon, monazite, xenotime), nor are Re and Os mobilized beyond the margins of individual crystals during solid-state recrystallization. Moreover, inheritance of older molybdenite cores, incorporation of common Os, and radiogenic Os loss are exceedingly rare, whereas inheritance, common Pb and Pb loss are common complications in U–Pb dating techniques. Therefore, molybdenite ages may serve as point-in-time markers for age comparisons.
Keywords: Re-Os chronometer; molybdenite (MoS2)